2017
DOI: 10.1063/1.4985875
|View full text |Cite
|
Sign up to set email alerts
|

Water liquid-vapor interface subjected to various electric fields: A molecular dynamics study

Abstract: Investigation of the effects of E-fields on the liquid-vapor interface is essential for the study of floating water bridge and wetting phenomena. The present study employs the molecular dynamics method to investigate the effects of parallel and perpendicular E-fields on the water liquid-vapor interface. For this purpose, density distribution, number of hydrogen bonds, molecular orientation, and surface tension are examined to gain a better understanding of the interface structure. Results indicate enhancements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 56 publications
1
9
2
1
Order By: Relevance
“…With this scaling relationship and the data demonstrated in Figure b, considering constant interfacial dimension and constant temperature, we could estimate a decreasing trend in the surface tension when external E‐field is applied, and the trend should appear differently depending on the type of the electrode which faces the water surface. This decreasing trend in surface tension agrees with both Stockmayer fluid surfaces and the TIP4P/2005 water surfaces in the presence of a perpendicular uniform E‐field. There appears no molecular‐level theory that can quantitatively interpret the mechanism for the change in the surface tension due to E‐field.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…With this scaling relationship and the data demonstrated in Figure b, considering constant interfacial dimension and constant temperature, we could estimate a decreasing trend in the surface tension when external E‐field is applied, and the trend should appear differently depending on the type of the electrode which faces the water surface. This decreasing trend in surface tension agrees with both Stockmayer fluid surfaces and the TIP4P/2005 water surfaces in the presence of a perpendicular uniform E‐field. There appears no molecular‐level theory that can quantitatively interpret the mechanism for the change in the surface tension due to E‐field.…”
Section: Resultssupporting
confidence: 81%
“…We present bulk densities ρ O B data as the function of the applied potential differences in Figure a. We found that, compared with their 0 V bulk value, the density decreases by 0.5% when electrodes voltage difference increases to 9 V. Our finding disagree with the argument in a recent MD study, in which bulk water density was reported unchanged under foreign uniform E‐field up to 1.2 V/nm . Meanwhile, the decreasing trend of the liquid water is consistent with that of the dipolar Stockmayer liquid‐ vapor coexistence system under applied uniform external E‐field …”
Section: Resultscontrasting
confidence: 70%
See 2 more Smart Citations
“…Δϕ is the voltage difference between cathode and anode, w 1090 is the 10~90 width of the water surface, χ1090 and stand for the water surface potential and surface dipolar polarization density difference, E0 is the strength of E-field in the vapor/vacuum region between electrodes and water surfaces, Ep is the strength of E-field within water film due to bulk polarization. Numbers in parentheses are 95% confidence errors for the last digits shown 水表面氢键网络结构也相应的调整 [34] : 一方面, 表面外 层水分子中的外露氢原子, 在电场作用下向块体水接 近, 拓宽氢键网络分布; 另一方面, 表面外层水分子中 氧原子直接在外电场作用下接近内层水分子中旋转外 露的氢原子, 拓宽氢键网络分布. 外电场下表面水分子 氢键网络结构的调整或表面偶极极化紧密关联着水的 表面电势分布函数的变化, 具体表现为电势分布函数在 水表面区域随外电场增大的调整(例如, -3.9 nm<z< -3.5 nm 区域电势分布的下移, 3.5 nm<z<3.9 nm 区域 电势分布的上移), 值得注意的是, 上下平移调整的量 值相对各个体系表面电势(见表 1)的绝对值要小(最多占 20%).…”
Section: 引言unclassified